Authentic advice for authentic problems? Legal information in Australian classroom drug education - Farrugia, A.; Seear, K.; Fraser, Suzanne (Informa Healthcare, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. This article examines the legal information provided in Australian alcohol and other drug (AOD) classroom education documents. We focus first on the technical presentation of the information, analysed using Petraglia’s notion of ‘authenticity’ and, second, on the constitution of particular ‘problems’, analysed using Bacchi’s concept of ‘problematisation’. We argue that in working towards deterrence, drug education provides legal information in two ways. First, much of the information focuses on the legal status of drugs, warning young people about the illegality of drugs. Second, information is communicated through structured group activities posed as creating opportunities for discussion. We argue that these strategies aim for a goal of deterrence and that this fits awkwardly with Australia’s avowed commitment to harm reduction drug policies. We argue further that young people’s relationship with the legal aspects of AOD use is too complex for these approaches and the goal of deterrence generally to be productive. In contrast, we propose an approach to drug education that includes a process of open problematisation in which students are invited to consider all aspects of use including the current regulation of drugs. We argue that approaching drug education in this way may more effectively inform about current legal arrangements and encourage the identification of potential problems and solutions more relevant to the lives of its audiences.